(untitled) (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2025)
This study examines how Indonesian Islamic influencers construct authority claims within algorithmically-mediated digital spaces, and how religious audiences navigate the relationship between digital authority and institutionally-rooted Islamic traditions. Employing netnographic methodology combined with algorithmic analysis and institutional interviews, we analyze five prominent Islamic content creators across YouTube, Instagram, and TikTok platforms over an 18-month period. Our findings reveal that Islamic authority in digital environments emerges through dynamic negotiation among: (1) content creators’ rhetorical authority strategies; (2) algorithmic visibility mechanisms; and (3) audience interpretive frameworks rooted in Indonesian institutional traditions. Rather than representing wholesale displacement of institutional Islamic authority, digital authority constitution involves sophisticated engagement with multiple legitimation mechanisms. The study offers practical insights for Islamic institutions navigating digital transformation and policy implications for platform designers and regulators.